INTERNATIONAL ELECTION OBSERVATIONS AND ELECTION CONSOLIDATION IN AFRICA: THE NIGERIAN EXPERIENCE (2015-2019) - Udeuhele, Godwin Ikechukwu; Ibiam, Okechukwu Egwu (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Whereas countries in other regions of the globe have seemingly perfected their act in maximizing the opportunities provided by democracy via free, fair and credible elections; Nigeria albeit the entire African continent remain apparently marooned and relegated to the edge of the precipice of democratic instability occasioned mainly by compromised election management system that is perceptively tied to the apron of the incumbent political party. Worried by the prevailing scenario of dearth of free, fair and credible elections in Africa there is an indictment on not only the electoral management bodies in different countries of Africa but also on politicians and political parties, especially the party in power. The exploratory research design was adopted; this paper also made use of qualitative method in its data collection and analyses. It made use of content analysis in extracting information from the secondary sources of data. The paper found that election observation is aimed at detecting any infractions in the electoral process; providing concerned bodies with remarks on the progress of the electoral process and decisions taken; and guaranteeing the integrity and neutrality of the electoral process. International election observation helps in building confidence in the transparency of the process. For international election observation to contribute in legitimizing the election process; building confidence; improving the prospects for democratization; enhancing the electoral process; and reducing or preventing conflict there is need to make the outcome of international election observation count in the overall legitimization of the result of the election so as to deter future compromise and manipulation of the process. Here in lay the expected usefulness of the observer mission. Till this begins to be seen to happen, international election observation will remain a mere ritual and a charade without any useful impact on democratic consolidation in Africa.